Pedagogies and Practices of Teaching Girlhood Studies. Issue 3 (1st December 2022) - Aguiló-Pérez, Emily R.; Reid-Walsh, Jacqueline
Abstract : Girlhood Studies, as an academic discipline, is continually growing. Since some educational institutions include girls' studies as part of a special curriculum, an academic program, a certificate course, a minor, or as part of Women's Studies or Gender Studies, Girlhood Studies has a presence in academia although at this stage rarely in an autonomous department. This interest in the pedagogies and practices of teaching Girlhood Studies is an important aspect of its growth as a field of study not only at the university level but also in other academic settings and outside of them, be they workshops, special programs for girls, and summer camps, among others. Depending on these formal and informal educational contexts, the discussion of approaches to teaching Girlhood Studies ranges from the theoretical to those that outline hands-on projects that invite and promote the discussion of girlhood. As Claudia Mitchell (2021) states in her editorial "What can Girlhood Studies be?" the research and scholarly work in Girlhood Studies "stands as its own theoretical and practical area" (vi) that warrants its study and teaching and that prompted the production of this special issue on teaching Girlhood Studies.